2022
DOI: 10.1002/adsu.202200067
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Engineering in Novel Fluorite‐Type Rare Earth High‐Entropy Oxides (RE‐HEOs) with Computational and Experimental Validation for Photocatalytic Water Splitting Applications

Abstract: Five different rare‐earth‐based nanocrystalline high entropy oxides (HEOs) with fluorite structure and average crystallite sizes between 6 and 8 nm are prepared and their photocatalytic behavior toward azo dye degradation and photoelectrochemical water splitting for hydrogen generation is examined. The cationic site in the fluorite lattice consists of five equimolar elements selected from the group of rare‐earth elements including La, Ce, Pr, Eu, and Gd and second‐row transition metals, Y and Zr. The studied H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 120 publications
1
35
0
Order By: Relevance
“…High-entropy oxides similar to other high-entropy compounds can act as catalysts in reactions of oxygen and hydrogen release from water . High-entropy RE oxides were also reported to be advanced catalysts for water splitting applications due to their high band gap flexibility …”
Section: Introductionmentioning
confidence: 99%
“…High-entropy oxides similar to other high-entropy compounds can act as catalysts in reactions of oxygen and hydrogen release from water . High-entropy RE oxides were also reported to be advanced catalysts for water splitting applications due to their high band gap flexibility …”
Section: Introductionmentioning
confidence: 99%
“…The calculations show that the energy difference between the VB and CB in the case of the SCNPTO was 2.69 eV, while that in the case of the SLTO was 3.05 eV. Recently it has been reported that the presence of Pr ions tends to lower the band gap in high-entropy oxides [ 50 ]. The much higher band gap in the case of the La-doped material is beneficial in preventing the recombination of electrons and holes to a greater extent than the SCNPTO, leading to a more efficient photocatalytic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] There is an immense amount of high entropy oxide materials (200+) that may show interesting optical properties. [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] For example, the stabilization of a high entropy sesquioxide ceramic phosphor has been shown to exhibit multi‐wavelength emission with a high degree of optical transparency in the visible region. [ 42 ] On the other hand, Ce‐doped RE‐based oxides have been observed to have narrow band gaps with absorption over the entire visible spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 , 39 ] Additionally, RE high entropy oxides with multiple optically active cations have shown improved photocatalytic performance when compared to similar single fluorite and equivalent mixed oxides. [ 41 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation